(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
Tourism is an important field of social life in terms of organizing people’s recreation, expanding cultural communication, creating workplaces, improving socio-economic conditions, solving ecological problems and ensuring sustainable human development. Tourism is one of the major sources of foreign currency inflows. In order to ensure the continuous development of tourism, it is necessary to have a scientifically approved sustainable worldview and build the tourism system on its basis. Therefore, the complete analysis of the worldview of tourism, the scientific substantiation of the principles and approaches, the prediction of expected results is actual and has practical significance. In order to solve the problem, in the formulation of the tourism concept preference is given to political, moral, aesthetic and scientific concepts and to the provisions of philosophy, as well as the idea of sustainable tourism, which is formed on the basis of these provisions. The components of tourism form a whole working as a living organism on scientifically based principles. The mentality of people formed on the basis of state policy and national moral norms are important for inbound tourism. The norms of morality and aesthetics, the way of thinking formed on their basis, the relations, the needs and the their satisfaction play an exceptional role in shaping the worldview of tourism. The role of principles developed by ethics and aesthetics has a tendency to grow very fast. And in general, tourism gets more moral, aesthetic and humanistic content. Humanism, endowed with universal values, transcends state borders, brings national, ethnic, cultural differences into a common field of cooperation, helps to find common ground between them, which helps to overcome stereotypes and traditions, makes an important attraction for the development of tourism instead of creating contradictions. The worldview of tourism at a certain level of development is the basis for sustainable tourism development.